Human T-lymphotropic virus (HTLV) research in cervical-vaginal discharge samples from women, in Belém, Pará, Brazil (Research, Society and Development, 2021)
Pará is among the Brazilian states with the highest prevalence rates of infection by the human T-lymphotropic virus (HTLV) in populations where this virus has already been investigated. HTLV infection generally has a higher prevalence in women over 40 and in a stable relationship. Furthermore, women are more susceptible to acquiring the virus through sexual intercourse. In this context, this study aimed to detect the HTLV provirus in vaginal-cervical discharge, with subsequent confirmation of the infection in blood samples, thus aiming to propose a new methodology for tracking the infection. A total of 400 women were investigated from November 2015 to December 2019, in Belém, Pará, Brazil. The vaginal-cervical discharge was collected during the Papanicolaou test (Pap test), and the peripheral blood, during posterior contact. After collection, the DNA of the samples was extracted and molecular analysis by Nested-PCR was performed, followed by a enzymatic digestion by Taq I, for detection of the infection by HTLV-1 or HTLV-2. Five (1.25%) of the 400 women tested positive for HTLV in vaginal-cervical discharge, three of them being HTLV-1 and two HTLV-2. Due to inaccessibility, it was only possible to confirm the blood infection in one of these five women. Our findings suggest that it is possible to use cervical-vaginal discharge samples as an alternative screening test for HTLV infection in women.